2020
DOI: 10.1038/s41598-020-75526-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the main PSA glycoforms in aggressive prostate cancer

Abstract: Serum levels of prostate specific antigen (PSA) are commonly used for prostate cancer (PCa) detection. However, their lack of specificity to distinguish benign prostate pathologies from PCa, or indolent from aggressive PCa have prompted the study of new non-invasive PCa biomarkers. Aberrant glycosylation is involved in neoplastic progression and specific changes in PSA glycosylation pattern, as the reduction in the percentage of α2,6-sialic acid (SA) are associated with PCa aggressiveness. In this study, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…The results indicated that levels of serum PSA sialylated glycoforms bearing GalNAc moieties (LacdiNAc) were raised in aggressive PCa patients. Concomitantly, levels of disialylated core fucosylated biantennary structures with α2,6-linked sialic acid, which were previously indicated as major PSA glycoforms characteristic for standard PSA from healthy men, were significantly lowered in aggressive PCa (Table 1) [79].…”
Section: Sialylated N-glycansmentioning
confidence: 64%
See 1 more Smart Citation
“…The results indicated that levels of serum PSA sialylated glycoforms bearing GalNAc moieties (LacdiNAc) were raised in aggressive PCa patients. Concomitantly, levels of disialylated core fucosylated biantennary structures with α2,6-linked sialic acid, which were previously indicated as major PSA glycoforms characteristic for standard PSA from healthy men, were significantly lowered in aggressive PCa (Table 1) [79].…”
Section: Sialylated N-glycansmentioning
confidence: 64%
“…This approach may lead to the establishment of new biomarkers with higher specificity for early cancer detection or for diagnosis in precancerous lesions [134,135]. Such research has become possible to carry out using newly developed, high-throughput platform technologies, which additionally enable the effective analysis of large sample cohorts [79,134]. Numerous studies have investigated whether a cancer-specific glycosylation pattern on PSA can be used to differentiate between BPH and PCa [75,133].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Kekki et al reported a significant increase in PSA fucosylation in PCa tissue compared to benign tissue and in urine from PCa patients compared to BPH patients using a nanoparticle‐based AAL‐immunoassay for analyzing the fucosylation of PSA 34 . Gratacos‐Mulleras et al characterized serum PSA glycoforms with hydrophilic interaction liquid chromatography and showed an important decrease of the disialylated core fucosylated biantennary structures with α2,6‐sialic acid and an increase of the α2,3‐disialylated core fucosylated biantennary and α2,3‐monosialylated noncore fucosylated structures in patients with aggressive PCa compare to PSA from healthy individuals' seminal plasma 35 . Since high levels of PSA exist in urine, analysis of glycosylations in urinary PSA could be a promising approach for biomarker discovery 36 .…”
Section: Discussionmentioning
confidence: 99%
“…-monosialylated noncore fucosylated structures in patients with aggressive PCa compare to PSA from healthy individuals' seminal plasma 35. Since high levels of PSA exist in urine, analysis of glycosylations in urinary PSA could be a promising approach for biomarker discovery 36.…”
mentioning
confidence: 99%
“…Previous studies have shown the significance of glycosylation for patient stratification and identification of novel biomarkers and therapeutic targets [41] , [42] . As example, altered sialylation and fucosylation have been used to improve the predictive value of PSA [86] , [87] , [88] . Targeting sialyl-Tn (STn) glycoforms of plasminogen in the serum of patients holds potential for non-invasive clinical diagnosis of individuals with gastric precancerous lesions [89] .…”
Section: Oncoproteogenomics Toward Neoantigen Discoverymentioning
confidence: 99%